Results of experimental research of process of braking the wheeled tractor «Fendt 936 Vario» - Самородов, Вадим Борисович; Бондаренко, Анатолій Ігорович (Technology audit and production reserves, 2014)
The process of handling longitudinal and lateral accelerations, resulting from the experimental research of the braking process of tractor «Fendt 936 Vario» with hydrostatic-mechanical transmission was described. To automate the processing of data, obtained from accelerometers, Butterworth low-pass filter, in particular free «Butterworth filter» software was used. The algorithm of this program is based on the discrete Fourier transformation, which is widely used in the statistics, time series analysis. Values of braking distance and maximum deviation from the desired trajectory during service and emergency braking on roads with different coupling coefficient (dry asphalt, wet asphalt, snow) were determined. A comparative analysis of theoretical results with experimental is conducted, and it was found that error in determining the braking distance value when service braking does not exceed 9,65%, emergency — 9,95 %; error in determining the deviation of the desired trajectory when service braking does not exceed 9,91 %, emergency — 8,33 %. Increasing the change intensity of control parameters of hydrostatic-transmission hydromachines when service braking (transition from the I slowing level to the IV) leads to reducing the braking distance and increasing the deviation of the desired trajectory. During the service braking there is an insignificant increase in braking distance — up to 3,79 % and an increase in deviation from the desired trajectory — up to 25 % when changing road conditions towards a decrease in the coupling coefficient of wheel with the supporting surface as a result of artificial limitation of tractor deceleration by the control parameters of hydrostatic-transmission hydromachines and their low change intensity. The above findings allow to get a broader understanding of the braking process of tractor «Fendt 936 Vario» and enhance the occupational safety of operators-drivers of these tractors.